Aging impairs CD8 T cell responses in adoptive T-cell therapy against solid tumors - Kadyrzhanova, Gulfiya; Tamai, Miho; Sarkar, Shukla; Kalra, Rajkumar Singh; Ishikawa, Hiroki (Frontiers in Immunology, 2025)
Age-associated defects in T cell-mediated immunity can increase the risk of cancers, but how aging influences adoptive T-cell therapy (ACT) for cancers remains unclear. Here, using a mouse model of melanoma, we demonstrate that aging diminishes anti-tumor activity of engineered CD8 T cells expressing a tumor-specific T cell receptor (CD8 TCR-T cells) in ACT for solid tumors. Aged CD8 TCR-T cells cannot control tumor growth in either young or aged mice. Aged CD8 TCR-T cells are unable to accumulate efficiently in tumors and have higher tendency to become terminally exhausted T cells with lower expression of endothelial PAS domain-containing protein 1 (Epas1) compared to young cells. Crispr-mediated ablation of Epas1 promotes terminal exhaustion of young CD8 T cells in tumors, diminishing their anti-tumor activity in young mice. Conversely, retroviral expression of Epas1 enhances anti-tumor activity of aged CD8 TCR-T cells. These findings suggest that aging-induced reduction of Epas1 expression impairs anti-tumor activity of CD8 T cells in ACT against solid tumors, which can be therapeutically improved by expression of exogenous Epas1.